Clinical Profile of Biliary Ascariasis Patients and Their Outcome Following Conservative Treatment in Medicine Units of a Tertiary Level Hospital - Khondaker, Mohammad Faiz Ahmad; Sayeed, Md. Abu; Nayeem, Abu; Sardar, Mohammad Hafiz (Journal of Shaheed Suhrawardy Medical College, 2012)
J Shaheed Suhrawardy Med Coll, 2011; 3 (1): 13-17 DOI: http://dx.doi.org/10.3329/jssmc.v3i1.12054